Applicability of technology acceptance in knowledge management implementation - Mohamed Razi, Mohamed Jalaldeen (2013)
Individual acceptance for technology adoption is well documented. However, though knowledge management processes highly depend on information technology use, the importance of individual acceptance is not thoroughly studied in knowledge management context. With the intention of filling this gap, the researcher attempts to verify the relationship between individual acceptance and intention to be involved in KM by using structural equation modelling (SEM). For this purpose, data were collected from 313 executive level organizational members from the telecommunication industry of Sri Lanka. The finding shows that both performance expectancy of KM and Effort expectancy of KM are positively related with intention to be involved in KM processes.